(untitled) (Research, Society and Development, 2021)
The present work aims to demonstrate the step by step of the construction of a tactile educational game for students with visual impairment (DV) who are included in regular classrooms of the fifth year of Elementary School. The tactile charts were produced to collaborate with the learning and possibility of abstraction of the content of the “Constellations of the Zodiac” of Astronomy. For the creation of the adapted game, images were used as visual references and low-cost resources. For the optimization of the process, we count on the help of an academic with DV, with previous handling of different materials suggested for the production of the didactic game, indicating, thus, the best perceptions regarding the dimensions and tactile sensations to be used for the identification of the constellations and position of transcripts in Braille. From the described process of construction of this resource, we affirm that the tactile materials elaborated, reached the purposes when applied to the student with participating DV, stimulating their learning process of the theme focused on the teaching of Astronomy, because definitions about the constellations can be considered complex for students with DV, being practically impossible to develop the notion of these characteristics without the aid of different tools. This applied research finds that in the area of ​​science education there is still a need for the production of adapted tactile games and teaching resources for students with DV for better awareness of the phenomena that surround us.